Etnografia de uma lei: o ensino de história e cultura afro-brasileira e indígena - Santos, Tamires Cristina dos (2019)
The Law and Directives for the Brazilian Educational System (Lei de Diretrizes e Bases da Educação Nacional/LDB), promulgated on December 20, 1996, which establishes national educational guidelines for the contents of the curricula of the public and private schools network in Brazil, was amended by Law 10.639/2003 and subsequently by Law 11.645/2008, establishing respectively the obligation to teach and learn about the History and Culture of Afro-Brazilian, African and Indigenous Peoples of Brazil in Basic Education. This ethnographic research sought to establish a dialogue with different agents who, directly or indirectly, were part of the process that established the law 11.645. From the fieldwork carried out at SECADI / MEC with its Technicians in Educational Affairs, documents collected in the MEC, and conversations with Indigenous leaderships, the aim was to learn about different discourses and practices that are mobilized around the law.